2009
DOI: 10.3174/ajnr.a1413
|View full text |Cite
|
Sign up to set email alerts
|

Graves Ophthalmopathy: The Bony Orbit in Optic Neuropathy, Its Apical Angular Capacity, and Impact on Prediction of Risk

Abstract: BACKGROUND AND PURPOSE:Optic neuropathy (ON), a serious complication of Graves ophthalmopathy, is often subclinical and masked by symptoms of orbitopathy. We examined herein bony and soft-tissue CT features associated with ON, including an angular assessment of orbital apex capacity, and their usefulness in the risk prediction of ON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
59
4
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 10 publications
6
59
4
12
Order By: Relevance
“…In our study, although the subjective orbital apex CI detected DON with 80.6% sensitivity for scores 1 or 2, none of the 36 affected orbits presented grade 3 apical crowding. These findings are remarkably different from previous studies using the Nugent subjective score to detect DON, 1,3,9,15 probably due to differences in subjective criteria for defining and grading apical crowding. While it seems clear that the Nugent apical crowding score is useful to raise suspicion of the presence of DON, it does not provide a clear definition of the position along the orbit where the coronal plane is used to determine it, nor does it provide a clear differentiation between grades 1, 2, and 3.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…In our study, although the subjective orbital apex CI detected DON with 80.6% sensitivity for scores 1 or 2, none of the 36 affected orbits presented grade 3 apical crowding. These findings are remarkably different from previous studies using the Nugent subjective score to detect DON, 1,3,9,15 probably due to differences in subjective criteria for defining and grading apical crowding. While it seems clear that the Nugent apical crowding score is useful to raise suspicion of the presence of DON, it does not provide a clear definition of the position along the orbit where the coronal plane is used to determine it, nor does it provide a clear differentiation between grades 1, 2, and 3.…”
Section: Discussioncontrasting
confidence: 56%
“…Other researchers have reached similar conclusions. 1,9 Finally, our study shows that CI is more efficient at detecting DON than the linear muscle index described by Barrett et al 10 In their study, a muscle index of 67% or greater indicated compressive neuropathy and had a diagnostic sensitivity of 67%. 10 In a previous study using MDCT to determine the sensitivity and specificity of the muscle index in a similar set of patients, we found that a muscle index of 60% provided the best combination of sensitivity/specificity (79% and 72%, respectively).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations